2011
DOI: 10.1097/rhu.0b013e318214b6b5
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine Use and Decreased Risk of Diabetes in Rheumatoid Arthritis Patients

Abstract: Our findings support the potential benefit of hydroxychloroquine in attenuating the risk of diabetes in rheumatoid arthritis patients. Further work is needed to determine its potential preventive role in other groups at high risk for diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 28 publications
1
52
1
5
Order By: Relevance
“…Notably, sevelamer carbonate reduced intracellular serum AGEs, well established proinflammatory compounds (4). The fact that sevelamer carbonate, but not calcium carbonate, reproduced the findings of dietary AGE restriction constitutes a potentially important new finding that could have therapeutic implications for the metabolic syndrome and other chronic conditions associated with increased oxidant stress and inflammation (43,44). The fact that reducing AGEs by two independent methods results in improvements in glucose metabolism and reactive oxygen species/inflammation adds credibility to the hypothesis that this action of sevelamer carbonate was due to the binding of AGEs in the intestinal contents and elimination of AGEs, rather than an effect on bile-acid acids and phosphate uptake.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, sevelamer carbonate reduced intracellular serum AGEs, well established proinflammatory compounds (4). The fact that sevelamer carbonate, but not calcium carbonate, reproduced the findings of dietary AGE restriction constitutes a potentially important new finding that could have therapeutic implications for the metabolic syndrome and other chronic conditions associated with increased oxidant stress and inflammation (43,44). The fact that reducing AGEs by two independent methods results in improvements in glucose metabolism and reactive oxygen species/inflammation adds credibility to the hypothesis that this action of sevelamer carbonate was due to the binding of AGEs in the intestinal contents and elimination of AGEs, rather than an effect on bile-acid acids and phosphate uptake.…”
Section: Discussionmentioning
confidence: 95%
“…Más frecuentemente se la utiliza como coadyuvante con otros FAME, como metotrexate (MTX), leflunomida (LFN) o sulfasalazina 32 . Además, recientemente se han descrito beneficios de este medicamento vinculados a su acción sobre el metabolismo lipídico y la insulinoresistencia en pacientes con AR, semejante a lo descripto en el LES 33 . Por otro lado, el uso de HCQ en combinación con otros FAME está bien documentado en la literatura.…”
Section: Hidroxicloroquina Y Artritis Reumatoideunclassified
“…26 In addition, the treatment of the systemic infl ammation of RA is known to be benefi cial, especially with the use of hydroxychloroquine and anti-TNF. [27][28][29] Some studies have also shown that the prevalence of type 1 DM is higher in patients with RA, especially in the subgroup positive for the anti-cyclic citrullinated peptide (anti-CCP) antibody. That risk can be attributed to an allele shared by both diseases, acting like a common risk factor in the pathogenesis of both diseases.…”
Section: Diabetes Mellitusmentioning
confidence: 99%